Implementasi implementasi manajemen kelas berbasis mindfulness untuk meniningkatkan hasil belajar peserta didik kelas VII dalam pembelajaran pendidikan agama katolik di SMPN 1 Nubatukan - Maria Elisabeth Wesan Raring; Benedikta Yosefina Kebingin; Yosep Belen Keban (Improvement: Jurnal Ilmiah untuk Peningkatan Mutu Manajemen Pendidikan, 2025)
This study aims to describe the implementation of mindfulness-based classroom management in Improving the Learning Outcomes of Students in the Kleas VII Catholic Religious Education Subject at SMP Negeri 1 Nubatukan. The background of this research is based on the challenge of creating an effective learning environment, where students often lack focus or concentration and have difficulty in applying the values of Catholic teachings in daily life. The mindfulnsess approach was chosen as a solution to improve concentration, emotion regulation, and student involvement in learning. This study uses a qualitative method with observation, interview, and documentation data collection techniques. The research subjects included, the principal, PAK teachers, and five students of grade VII. The results of the study showed that mindfulness-based classroom management succeeded in improving students' concentration, emotional intelligence, and ability to socialize. In addition, this approach also has a positive impact on student learning outcomes, both cognitive, affective, and psychomotor aspects. The findings of this study support several previous studies that have stated that mindfulness can improve learning outcomes, although there are other studies that show its impact on psychological aspects more significantly than academics.